ChemInform Abstract: Biosilica as an Efficient Heterogeneous Catalyst for ipso‐Hydroxylation of Arylboronic Acids. Issue 30 (July 2015) - Mahanta, Abhijit; Adhikari, Pooja; Bora, Utpal; Thakur, Ashim Jyoti
Abstract A green synthesis of phenols from areneboronates is presented by using aqueous H2O2 as an oxidant and biosilica as a catalyst.